Visual Impairment and Objectively Measured Physical Activity in Middle-Aged and Older Adults. (10th April 2021) - Cai, Yurun; Schrack, Jennifer A; Wang, Hang; E, Jian-Yu; Wanigatunga, Amal A; Agrawal, Yuri; Urbanek, Jacek K; Simonsick, Eleanor M; Ferrucci, Luigi; Swenor, Bonnielin K
Abstract: Background: Vision loss is associated with increased risk of falls and restricted physical activity, yet the relationship between multiple vision measures and objectively measured physical activity, especially activity patterns, in mid-to-late life is not well understood. Method: This study included 603 participants aged 50 years and older (mean age = 73.5) in the Baltimore Longitudinal Study of Aging who had the following assessments: presenting and best-corrected visual acuity, contrast sensitivity, visual fields, stereo acuity, and free-living physical activity using a wrist-worn ActiGraph accelerometer for 7 days. Linear regression models were used to examine the association between vision measures and daily activity counts, active minutes, and activity fragmentation (defined as an active-to-sedentary transition probability), adjusting for potential confounders. Mixed-effects models estimated differences in activity by time of day comparing those with and without each visual impairment. Results: In the fully adjusted model, worse presenting visual acuity, contrast sensitivity, and visual fields were associated with fewer activity counts, less active time, and more fragmented activity patterns ( p < .05 for all). Participants with presenting or best-corrected visual acuity impairment had 19.2 and 29.3 fewer active minutes ( p = .05 and p = .03, respectively) per day. Visual field impairment was associated with 268 636 fewer activity counts ( p = .02), 46.2 fewer active minutes ( p = .02) per day, and 3% greater activity fragmentation ( p = .009). Differences in activity levels tended to be greatest from 6 am to 6 pm ( p < .05). Conclusions: Older adults with visual impairment have restricted and more fragmented patterns of daily activity. Longitudinal studies to quantify the long-term impacts of visual impairments on activity decline are warranted.